Metal oxide gradient coated sodium ferric fluorophosphate material as well as preparation method and application thereof
By using metal oxide gradient coated in the positive electrode material of sodium ion battery, the ZnxAl(4-2x)/3O2 gradient coating is deposited using ALD technology, the low energy density of the positive electrode material of sodium ion battery is solved. and the problem of poor circulation performance have achieved improvements in structural stability and mass transfer efficiency.
Patent Information
- Application Number
- CN202411544541.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-31
- Publication Date
- 2025-02-07
- Estimated Expiration
- 2044-10-31
AI Technical Summary
The existing sodium ion battery positive electrode materials have problems such as low energy density and poor circulation performance. Moreover, the preparation method of lithium ion battery positive electrode materials cannot be directly used in sodium ion batteries, which can easily lead to volume changes and cracks during charging and discharging.
Sodium Ferrophosphate material coated with metal oxide gradient, ZnxAl(4-2x)/3O2 gradient coating was deposited on the surface of Sodium Ferrophosphate powder through ALD atomic deposition technology to regulate the ratio of aluminum and zinc of the precursor , to improve the structural stability and mass transfer efficiency of the material.
It improves structural stability and mass transfer efficiency during material circulation, reduces the interface resistance between the material and the electrolyte, improves the comprehensive performance of the positive electrode material, and reduces production costs and battery management costs.
Smart Images

Figure CN119400829A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of sodium ion battery positive electrode materials, and in particular to a metal oxide gradient-coated sodium iron fluorophosphate material, and a preparation method and application thereof. Background Art
[0002] With the rapid development of industry, traditional fossil energy is becoming increasingly exhausted, and various new types of renewable energy have been widely used. However, the use of new energy sources such as wind energy and solar energy to generate electricity is irregular in time and space. Rechargeable batteries have the ability to convert electrical energy into chemical energy for storage. Among them, lithium-ion batteries are well developed and have mature technology. They are an ideal choice for energy storage power stations. Various new materials have appeared in lithium-ion battery positive electrode materials. For example: Chinese patent document CN111883748A discloses a method for coating the surface of lithium-ion battery positive electrode powder material with an oxide film; Chinese patent document CN102244231A proposes using atomic layer deposition technology to deposit surface modification substances on the surface of positive electrode active materials. However, the surface of the material prepared by this patent is a single substance deposition, which has certain performance and application limitations;
[0003] As the price of lithium ore gradually rises, the high storage cost and resource shortage hinder the application of lithium-ion batteries in large-scale energy storage power stations. As an emerging rechargeable battery, sodium-ion batteries have a low energy density, but for large-scale energy storage power stations, it is not a key issue. At the same time, sodium-ion batteries are abundant in resources and low in price. Their key technologies are not much different from those of lithium-ion batteries, and they have a good technical foundation. In addition, in the face of a more complex working environment, sodium-ion batteries can also achieve wide temperature range discharge and fast charging and discharging. Therefore, sodium-ion batteries are becoming the main choice for large-scale energy storage power stations. However, the main sodium-ion battery cathode materials currently available still face many challenges such as low energy density and poor cycle performance; compared with lithium-ion battery cathode materials, especially the common lithium iron phosphate materials, it is difficult to process sodium fluorinated iron phosphate materials with low conductivity and poor structural stability to obtain sodium-ion battery cathode materials. The preparation method of lithium-ion battery cathode materials cannot be applied to sodium-ion batteries. Direct application can easily cause sodium-ion batteries to change in volume and crack during charging and discharging. Summary of the invention
[0004] The purpose of the present invention is to address the deficiencies in the prior art and to provide a metal oxide gradient-coated sodium ferric phosphate material, a preparation method and an application thereof, which can simultaneously improve the structural stability and mass transfer efficiency during the material circulation process and reduce the interface resistance between the material and the electrolyte.
[0005] To achieve the above object, the technical solution adopted by the present invention is:
[0006] The first aspect of the present invention is to provide a metal oxide gradient coated sodium fluorophosphate material, the chemical formula of which is Na2FePO4F@Zn x Al (4-2x) / 3 O2; wherein, 0.3≤x≤1.4.
[0007] The second aspect of the present invention is to provide a method for preparing the above-mentioned metal oxide gradient-coated sodium fluorophosphate material, the steps comprising:
[0008] S1. After mixing anhydrous sodium acetate, sodium fluoride, ammonium dihydrogen phosphate and an iron source, a dispersant is added to perform sufficient ball milling and mixing, and then drying and pre-sintering are performed in sequence to obtain sodium fluoroferric phosphate powder;
[0009] S2, placing the sodium fluorophosphate iron powder in an ALD reaction chamber, evacuating the chamber and heating the chamber to 100-120° C.;
[0010] S3, under an inert atmosphere, depositing a mixed vapor of a precursor aluminum source and a precursor zinc source on the surface of the sodium fluoroferric phosphate powder, then introducing an inert gas to blow away the excess mixture of the precursor aluminum source and the precursor zinc source on the surface of the sodium fluoroferric phosphate powder; introducing a precursor oxygen source, and after performing an oxidation-reduction reaction with the mixture of the precursor aluminum source and the precursor zinc source on the surface of the sodium fluoroferric phosphate powder, introducing an inert gas to blow away the excess precursor oxygen source and side reaction products on the surface of the sodium fluoroferric phosphate powder; that is, completing one ALD deposition;
[0011] S4, repeating step S3, performing multiple ALD depositions, and gradually increasing the content of the precursor zinc source in the mixed vapor of the precursor aluminum source and the precursor zinc source during each ALD deposition, to obtain a sodium fluorophosphate material coated with a metal oxide gradient.
[0012] Preferably, in step S1, the molar ratio of the anhydrous sodium acetate, the sodium fluoride, the diammonium phosphate and the iron source is (1.0-1.5): (1.0-1.3): (1.0-1.5): (1.0-1.5).
[0013] Preferably, in step S1, the iron source includes at least one of ferrous oxalate, ferrous sulfate and ferrous chloride.
[0014] Preferably, in step S1, the mass ratio of the dispersant to the mixture is 1:(1-3); the dispersant includes: at least one of anhydrous ethanol, acetone, isopropanol, and N-methylpyrrolidone.
[0015] Preferably, in step S1, the rotation speed of the ball milling is 300-500 rpm, the time is 6-8 hours, and the mass ratio of the ball milling beads to the mixture is (8-10):1;
[0016] The drying process is carried out at a temperature of 60 to 100°C and a time of 8 to 14 hours;
[0017] The pre-sintering treatment includes: pre-passing protective gas at room temperature for 0.5 to 2 hours, heating to 350 to 450° C. at a rate of 3 to 5° C. / min, and then calcining for 2 to 6 hours; the protective gas includes: at least one of argon, hydrogen argon, nitrogen, and helium.
[0018] Preferably, in step S3, the flow rate of the inert gas during deposition is 50 mL / min, and the duration is 40 to 60 s; the flow rate of the inert gas during blow-off is 100 mL / min, and the duration is 80 to 120 s.
[0019] Preferably, the precursor aluminum source includes at least one of trimethylaluminum, dimethylethylaluminum, diethylaluminum, diisobutylaluminum, 2-aminopyridine diethylaluminum, 2-tert-butylaminomethylpyridine dimethylaluminum, pyrrole-2-imide dimethylaluminum, and diethylaluminum;
[0020] The precursor zinc source includes: at least one of diethyl zinc, dimethyl zinc, pyridine zinc complex, pyrimidine zinc complex, and nitrogen heterocyclic carbene zinc complex;
[0021] The precursor oxygen source includes at least one of H2O, O2, and O3.
[0022] Preferably, in steps S3 to S4, the number of ALD depositions is 8 to 10 times, wherein in the first ALD deposition, the content of the precursor zinc source in the mixed vapor is 20% to 40%, and in the last ALD deposition, the content of the precursor zinc source in the mixed vapor is 60% to 80%.
[0023] The third aspect of the present invention is to provide an application of the above-mentioned metal oxide gradient coated sodium fluorophosphate material or the metal oxide gradient coated sodium fluorophosphate material obtained by the above-mentioned preparation method in the positive electrode material of a sodium ion battery.
[0024] The present invention adopts the above technical solution, and has the following technical effects compared with the prior art:
[0025] (1) The present invention uses a method of pre-passing inert gas to avoid oxidation of ferrous iron during the sintering process, which would lead to a significant reduction in the specific capacity of the material, thereby improving the material yield.
[0026] (2) The present invention uses ALD atomic deposition technology to achieve the Zn2+ phase transition from the inner to the outer surface of the sodium fluorophosphate positive electrode material by successively adjusting the ratio of the two metal precursors. x Al (4-2x) / 3O2 gradient coating; the introduction of a certain proportion of a mixture of two metal precursors at the same time is conducive to the formation of a mixed metal oxide deposition layer with a tight interface and a smoother transition, making full use of the advantages of Al2O3's high mechanical strength and corrosion resistance, and ZnO's high electrical conductivity. The inner layer has a high Al2O3 content, which effectively improves the structural stability of the material during the cycle and effectively reduces the erosion and mechanical damage of the positive electrode material by the external environment; the outer layer has a high ZnO content, which is conducive to improving the mass transfer efficiency, reducing the interface resistance between the material and the electrolyte, and maximizing the comprehensive performance of the positive electrode material; the gradient coating can give full play to the respective advantages of the two metal oxides and maximize the performance of the positive electrode material; the material does not contain precious metals, has a low production cost, good safety performance, and a narrow discharge voltage range, which reduces the battery management cost and is suitable for large-scale power grid energy storage. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 The Zn prepared in Example 1 of the present invention x Al (4-2x) / 3 SEM image of O2 gradient coated sodium fluoroferric phosphate;
[0028] Figure 2 This is a comparison picture of the discharge curves of the coated sodium fluoroferric phosphate prepared in Example 1, Comparative Example 1, and Comparative Example 2 of the present invention. DETAILED DESCRIPTION
[0029] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0030] It should be noted that, in the absence of conflict, the embodiments of the present invention and the features in the embodiments may be combined with each other.
[0031] The present invention will be further described below in conjunction with the accompanying drawings and specific embodiments, but they are not intended to limit the present invention.
[0032] Example 1
[0033] This embodiment provides a method for preparing a sodium fluorophosphate material coated with a metal oxide gradient, the steps comprising:
[0034] S1, mixing anhydrous sodium acetate, sodium fluoride, ammonium dihydrogen phosphate and ferrous oxalate (the molar ratio of the anhydrous sodium acetate, the sodium fluoride, the ammonium dihydrogen phosphate and the ferrous oxalate is 1.0:1.0:1.0:1.0), adding a dispersant for sufficient ball milling, and sequentially performing drying and pre-sintering to obtain sodium fluoroferric phosphate powder;
[0035] The ball milling mixing was performed at a rotation speed of 500 rpm for 6 h, and a mass ratio of ball milling beads to the mixture was 8:1;
[0036] The drying temperature is 60°C and the drying time is 14 hours;
[0037] The pre-sintering treatment includes: pre-passing argon gas at room temperature for 1 hour, heating to 350° C. at a rate of 3° C. / min, and then calcining for 6 hours;
[0038] The mass ratio of the dispersant to the mixture is 1:1; the dispersant is a mixed solution of anhydrous ethanol and acetone in a volume ratio of 1:5.
[0039] S2, placing the sodium fluorophosphate iron powder in an ALD reaction chamber, evacuating the chamber and heating the chamber to 100° C.;
[0040] S3, under an inert atmosphere (flow rate of 50 mL / min, duration of 60 s), a mixed vapor of trimethylaluminum and diethylzinc is deposited on the surface of the sodium fluoroferric phosphate powder, and then an inert gas is introduced (flow rate of 100 mL / min, duration of 120 s) to blow away the excess trimethylaluminum and diethylzinc mixture on the surface of the sodium fluoroferric phosphate powder; H2O is introduced to perform an oxidation-reduction reaction with the trimethylaluminum and diethylzinc mixture on the surface of the sodium fluoroferric phosphate powder, and then an inert gas is introduced (flow rate of 100 mL / min, duration of 100 s) to blow away the excess H2O and side reaction products on the surface of the sodium fluoroferric phosphate powder; that is, one ALD deposition is completed;
[0041] S4. Repeat step S3 for a total of 9 ALD depositions, and gradually increase the content of diethyl zinc in the mixed vapor of the mixture of trimethylaluminum and diethyl zinc during each ALD deposition (the content of diethyl zinc in the mixed vapor is 20% in the first ALD deposition; the content of diethyl zinc in the mixed vapor is 60% in the last ALD deposition), thereby obtaining a metal oxide gradient-coated sodium fluorophosphate material.
[0042] Example 2
[0043] This embodiment provides another method for preparing a sodium fluorophosphate material coated with a metal oxide gradient, the steps comprising:
[0044] S1. After mixing anhydrous sodium acetate, sodium fluoride, ammonium dihydrogen phosphate and ferrous chloride (the molar ratio of the anhydrous sodium acetate, the sodium fluoride, the ammonium dihydrogen phosphate and the ferrous chloride is 1.0:1.1:1.3:1.0), adding a dispersant to fully ball-mill and mix, and sequentially performing drying and pre-sintering treatments, the mixture is sequentially subjected to ball-milling treatments, drying treatments and pre-sintering treatments to obtain sodium fluoroferric phosphate powder;
[0045] The ball milling mixing was performed at a rotation speed of 300 rpm for 8 h, and a mass ratio of ball milling beads to the mixture was 9:1;
[0046] The drying temperature is 80°C and the drying time is 12h;
[0047] The pre-sintering treatment includes: pre-passing hydrogen and argon at room temperature for 1.5 hours, heating to 400° C. at a rate of 4° C. / min, and then calcining for 4 hours;
[0048] The mass ratio of the dispersant to the mixture is 1:2; the dispersant is a mixed solution of acetone and isopropanol in a volume ratio of 1:1.
[0049] S2, placing the sodium fluorophosphate iron powder in an ALD reaction chamber, evacuating the chamber and heating the chamber to 120° C.;
[0050] S3, under an inert atmosphere (flow rate of 50 mL / min, duration of 40 s), a mixed vapor of dimethyl ethyl aluminum and dimethyl zinc is deposited on the surface of the sodium ferric fluorophosphate powder, and then an inert gas (flow rate of 100 mL / min, duration of 100 s) is introduced to blow away the excess dimethyl ethyl aluminum and dimethyl zinc mixture on the surface of the sodium ferric fluorophosphate powder; O2 is introduced to react with the dimethyl ethyl aluminum and dimethyl zinc mixture on the surface of the sodium ferric fluorophosphate powder, and then an inert gas (flow rate of 100 mL / min, duration of 80 s) is introduced to blow away the excess O2 and side reaction products on the surface of the sodium ferric fluorophosphate powder; that is, one ALD deposition is completed;
[0051] S4. Repeat step S3 for a total of 8 ALD depositions, and gradually increase the content of dimethyl zinc in the mixed vapor of the mixture of dimethyl ethyl aluminum and dimethyl zinc during each ALD deposition (the content of dimethyl zinc in the mixed vapor is 40% in the first ALD deposition and 80% in the last ALD deposition), to obtain a metal oxide gradient-coated sodium iron fluorophosphate material.
[0052] Example 3
[0053] This embodiment provides another method for preparing a sodium fluorophosphate material coated with a metal oxide gradient, the steps comprising:
[0054] S1. After mixing anhydrous sodium acetate, sodium fluoride, ammonium dihydrogen phosphate and an iron source (the molar ratio of the anhydrous sodium acetate, the sodium fluoride, the ammonium dihydrogen phosphate and the iron source is 1.5:1.3:1.2:1.2; the iron source is a mixture of ferrous oxalate and ferrous chloride in a molar ratio of 1:1), a dispersant is added for sufficient ball milling and mixing, and drying and pre-sintering are performed in sequence to obtain sodium fluoroferric phosphate powder;
[0055] The ball milling mixing was performed at a rotation speed of 400 rpm for 7 h, and a mass ratio of ball milling beads to the mixture was 10:1;
[0056] The drying temperature is 100°C and the time is 10h;
[0057] The pre-sintering treatment includes: pre-flowing nitrogen at room temperature for 2 hours, heating to 450° C. at a rate of 5° C. / min, and then calcining for 3 hours;
[0058] The mass ratio of the dispersant to the mixture is 1:3; the dispersant is a mixed solution of anhydrous ethanol and N-methylpyrrolidone in a volume ratio of 1:6.
[0059] S2, placing the sodium fluorophosphate iron powder in an ALD reaction chamber, evacuating the chamber and heating the chamber to 110° C.;
[0060] S3, under an inert atmosphere (flow rate of 50 mL / min, duration of 60 s), depositing a mixed vapor of diisobutylaluminum and diethylzinc on the surface of the sodium fluoroferric phosphate powder, then introducing an inert gas (flow rate of 100 mL / min, duration of 80 s) to blow away the excess diisobutylaluminum and diethylzinc mixture on the surface of the sodium fluoroferric phosphate powder; introducing H2O to carry out an oxidation-reduction reaction with the diisobutylaluminum and diethylzinc mixture on the surface of the sodium fluoroferric phosphate powder, and then introducing an inert gas (flow rate of 100 mL / min, duration of 120 s) to blow away the excess H2O and side reaction products on the surface of the sodium fluoroferric phosphate powder; that is, completing one ALD deposition;
[0061] S4. Repeat step S3 for a total of 10 ALD depositions, and gradually increase the content of diethyl zinc in the mixed vapor of the mixture of diisobutylaluminum and diethyl zinc during each ALD deposition (the content of diethyl zinc in the mixed vapor is 30% for the first ALD deposition and 70% for the last ALD deposition), to obtain a metal oxide gradient-coated sodium iron fluorophosphate material.
[0062] Comparative Example 1
[0063] This comparative example provides another method for preparing a sodium fluorophosphate material coated with a metal oxide gradient. Steps S1-S2 are the same as those in Example 1. In step S3, only trimethylaluminum is introduced, and only one ALD deposition is performed without gradient coating.
[0064] Comparative Example 2
[0065] This comparative example provides another method for preparing a sodium fluorophosphate material coated with a metal oxide gradient. Steps S1-S2 are the same as those in Example 1. In step S3, only diethyl zinc is introduced, and only one ALD deposition is performed without gradient coating.
[0066] Detection Example
[0067] 1. Morphology test
[0068] After the metal oxide gradient-coated sodium iron fluoride phosphate material prepared by the preparation method described in Example 1 was subjected to gold spraying treatment, the surface morphology of the sample was characterized using a German ZEISS GEMINI 500 scanning electron microscope. Figure 1 As shown, the material prepared by the preparation method described in Example 1 is spherical particles with a diameter of 2 to 3 μm.
[0069] 2. Battery cycle performance test
[0070] In order to test the electrochemical properties of the material, the sodium fluorophosphate material prepared by the preparation method described in Examples 1-3 and Comparative Examples 1-2 was used as the positive electrode to assemble the half-cell for electrochemical performance testing. First, 175 mg of sodium fluorophosphate material and 50 mg of SuperP were weighed respectively, ground in an agate mortar for about 20 min until fully mixed and transferred to a paste bottle, 500 mg of the prepared 5wt% PVDF NMP solution was added, and then about 800 μL of NMP solution was added, and magnetic stirring was performed for about 12 hours to a slightly viscous paste liquid. Subsequently, a 120 μm scraper was used to evenly coat the paste on the aluminum foil, and vacuum dried at 120 ° C for 12 hours. The obtained positive electrode sheet was formed into a positive electrode sheet with a diameter of 12 mm by a sheet punching machine. With the electrode sheet as the positive electrode, the sodium sheet as the negative electrode, the glass fiber as the separator, and 1.0M NaClO4 / EC-PC (volume ratio 1:1, 5.0Vol% FEC) as the electrolyte, CR2032 button cells were assembled in a glove box filled with argon.
[0071] The button cell is charged and discharged at a constant current of 0.2C (1C = 120mAh / g), with a voltage range of 2.0 to 4.0V. Its charge and discharge curve is as follows Figure 2 As shown; the charge and discharge results are shown in Table 1;
[0072] Table 1
[0073]
[0074] The surface of the sodium fluorophosphate material obtained in Comparative Example 1 has only a single Al2O3 coating layer, which can reduce the structural damage caused by the side reaction between the material and the electrolyte to a certain extent, but it does not significantly improve the conductivity of the material. During the battery charge and discharge test, a large polarization will occur and part of the capacity will be lost. As shown in Table 1, compared with the gradient coating, the first discharge specific capacity of the sodium fluorophosphate material coated with a single Al2O3 is lower, and the first coulomb efficiency is also relatively lower. The coating layer has a lower modification effect on the sodium fluorophosphate material than Zn x Al (4-2x) / 3 O2 gradient coating.
[0075] The surface of the sodium fluoroferric phosphate material obtained in Comparative Example 2 has only a single ZnO coating layer, which can improve the conductivity of the material to a certain extent and reduce the capacity loss caused by polarization. However, due to the large relative molecular mass of ZnO, it has a certain impact on the material's gram capacity, and the mechanical properties of ZnO are poor, and it may partially fall off during the paste or cycle period, and cannot play a normal modification role. As can be seen from Table 1, compared with the gradient coating, the first discharge specific capacity of the sodium fluoroferric phosphate material coated with a single ZnO is lower, and the first coulomb efficiency is also relatively reduced. The coating layer has a lower modification effect on the sodium fluoroferric phosphate material than ZnO. x Al (4-2x) / 3 O2 gradient coating.
[0076] The present invention utilizes ALD atomic deposition technology and gradually adjusts the ratio of the two metal precursors to achieve the Zn2+ phase transition from the inner to the outer surface of the sodium ferric fluoride phosphate cathode material. x Al (4-2x) / 3 O2 gradient coating and the introduction of a certain proportion of a mixture of two metal precursors are conducive to the formation of a mixed metal oxide deposition layer with a tight interface and a smoother transition, making full use of the advantages of high mechanical strength and corrosion resistance of Al2O3 and high electrical conductivity of ZnO. The inner layer has a high Al2O3 content, which effectively improves the structural stability of the material during the cycle. The outer layer has a high ZnO content, which is conducive to improving the mass transfer efficiency, reducing the interface resistance between the material and the electrolyte, and maximizing the comprehensive performance of the positive electrode material.
[0077] The above description is only a preferred embodiment of the present invention, and does not limit the implementation mode and protection scope of the present invention. For those skilled in the art, it should be aware that all solutions obtained by equivalent substitutions and obvious changes made using the description and illustrations of the present invention should be included in the protection scope of the present invention.
Claims
1. A metal oxide gradient coated sodium fluorophosphate material, characterized in that: The chemical formula is Na2FePO4F@Zn x Al (4-2x) / 3 O2; wherein, 0.3≤x≤1.
4.
2. A method for preparing the sodium fluorophosphate material coated with a metal oxide gradient as claimed in claim 1, characterized in that the steps include: S1. After mixing anhydrous sodium acetate, sodium fluoride, ammonium dihydrogen phosphate and an iron source, a dispersant is added to perform sufficient ball milling and mixing, and then drying and pre-sintering are performed in sequence to obtain sodium fluoroferric phosphate powder; S2, placing the sodium fluorophosphate iron powder in an ALD reaction chamber, evacuating the chamber and heating the chamber to 100-120° C.; S3, under an inert atmosphere, depositing a mixed vapor of a precursor aluminum source and a precursor zinc source on the surface of the sodium fluoroferric phosphate powder, then introducing an inert gas to blow away the excess mixture of the precursor aluminum source and the precursor zinc source on the surface of the sodium fluoroferric phosphate powder; introducing a precursor oxygen source, and after performing an oxidation-reduction reaction with the mixture of the precursor aluminum source and the precursor zinc source on the surface of the sodium fluoroferric phosphate powder, introducing an inert gas to blow away the excess precursor oxygen source and side reaction products on the surface of the sodium fluoroferric phosphate powder; that is, completing one ALD deposition; S4, repeating step S3, performing multiple ALD depositions, and gradually increasing the content of the precursor zinc source in the mixed vapor of the precursor aluminum source and the precursor zinc source during each ALD deposition, to obtain a sodium fluorophosphate material coated with a metal oxide gradient.
3. The preparation method according to claim 2, characterized in that: In step S1, the molar ratio of the anhydrous sodium acetate, the sodium fluoride, the diammonium phosphate and the iron source is (1.0-1.5): (1.0-1.3): (1.0-1.5): (1.0-1.5).
4. The preparation method according to claim 2, characterized in that: In step S1, the iron source includes at least one of ferrous oxalate, ferrous sulfate and ferrous chloride.
5. The preparation method according to claim 2, characterized in that: In step S1, the mass ratio of the dispersant to the mixture is 1:(1-3); the dispersant includes: at least one of anhydrous ethanol, acetone, isopropanol, and N-methylpyrrolidone.
6. The preparation method according to claim 2, characterized in that: In step S1, the rotation speed of the ball milling is 300-500 rpm, the time is 6-8 hours, and the mass ratio of the ball milling beads to the mixture is (8-10):1; The drying process is carried out at a temperature of 60 to 100°C and a time of 8 to 14 hours; The pre-sintering treatment includes: pre-passing protective gas at room temperature for 0.5 to 2 hours, heating to 350 to 450° C. at a rate of 3 to 5° C. / min, and then calcining for 2 to 6 hours; the protective gas includes: at least one of argon, hydrogen argon, nitrogen, and helium.
7. The preparation method according to claim 2, characterized in that: In step S3, the flow rate of the inert gas during deposition is 50 mL / min, and the duration is 40 to 60 s; the flow rate of the inert gas during blow-off is 100 mL / min, and the duration is 80 to 120 s.
8. The preparation method according to claim 2, characterized in that: The precursor aluminum source includes at least one of trimethylaluminum, dimethylethylaluminum, diethylaluminum, diisobutylaluminum, 2-aminopyridine diethylaluminum, 2-tert-butylaminomethylpyridine dimethylaluminum, pyrrole-2-imide dimethylaluminum, and diethylaluminum; The precursor zinc source includes: at least one of diethyl zinc, dimethyl zinc, pyridine zinc complex, pyrimidine zinc complex, and nitrogen heterocyclic carbene zinc complex; The precursor oxygen source includes at least one of H2O, O2, and O3.
9. The preparation method according to claim 2, characterized in that: In steps S3 to S4, the number of ALD depositions is 8 to 10 times, wherein in the first ALD deposition, the content of the precursor zinc source in the mixed vapor is 20% to 40%, and in the last ALD deposition, the content of the precursor zinc source in the mixed vapor is 60% to 80%.
10. Use of the metal oxide gradient coated sodium fluorophosphate material as claimed in claim 1 or the metal oxide gradient coated sodium fluorophosphate material prepared by the preparation method according to any one of claims 2 to 9 in a positive electrode material for a sodium ion battery.
Citation Information
Patent Citations
Composite positive electrode material for sodium ion battery and preparation method of composite positive electrode material
CN115863573A
High temperature solid phase method of ferrosodium flurophosphate for sodium ion battery
CN1948138A
Deposited sodium iron phosphate positive electrode material, and preparation method therefor and application thereof
WO2023060989A1